Successful Desensitization to mRNA COVID-19 Vaccine in a Case Series of Patients With a History of Anaphylaxis to the First Vaccine Dose - AlMuhizi, Faisal; Ton-Leclerc, Shaonie; Fein, Michael; Tsoukas, Christos; Garvey, Lene Heise; Lee, Derek; Ben-Shoshan, Moshe; Isabwe, Ghislaine A. C.; Copaescu, Ana M. (Frontiers in Allergy, 2022)
Background: Coronavirus disease (COVID-19) vaccines have recently been approved to curb the global pandemic. The risk of allergic reactions to the vaccine polyethylene glycol (PEG) component has raised significant public concern. Desensitization is suggested in cases of vaccine related hypersensitivity reactions. After comprehensive literature review on the topic, our aim was to establish a safe and effective desensitization protocol for patients with suspected or confirmed immediate type hypersensitivity reactions to the COVID-19 vaccine. Methods: Participants were referred to the McGill University Health Centre (MUHC) Allergy-Immunology department for clinical evaluation following a reported reaction to their first dose of Moderna mRNA-1273 or Pfizer-BioNTech BNT162b2 vaccines. They underwent skin prick testing with higher and lower molecular weight PEG and polysorbate 80, as per published protocols. Their second dose was administered following a desensitization protocol consisting of multiple dose-administration steps followed by a 60-minutes observation period. Results: Among a cohort of 142 patients with an increased risk for allergic reactions to the COVID-19 vaccines, 6 individuals were selected to undergo desensitization. All were female with allergic background including chronic spontaneous urticaria, anaphylaxis to medications and/or vaccines. The main symptom after their first dose was difficulty swallowing with lightheadedness or immediate urticaria, angioedema and/or dizziness. Two patients had positive skin testing. One patient was on chronic antihistamines which resulted in an inconclusive PEG skin test and the skin testing was negative for the 3 other patients. During the desensitization, two patients reported cutaneous symptoms of an immediate reaction and were managed with antihistamines. One of these patients also complained of ear pressure and had a drop in her systolic blood pressure, treated with intravenous fluids. Conclusion: This study suggests that some individuals with an immediate-type hypersensitivity reaction to their first dose of mRNA COVID-19 vaccine may safely receive their second dose using a desensitization protocol. The success of this desensitization protocol is a step forward in the fight against COVID-19, allowing more individuals to be immunized.